Activation of retinal angiogenesis in hyperglycemic pdx1 -/- zebrafish mutants - Wiggenhauser, Lucas; Qi, Haozhe; Cramer-Stoll, Sandra; Metzger, Lena; Bennewitz, Katrin; Poschet, Gernot; Krenning, Guido; Hillebrands, Jan-Luuk; Hammes, Hans-Peter; Kroll, Jens (Diabetes, 2020)
Progression from the initial vascular response upon hyperglycemia to a proliferative stage with neovacularizations is the hallmark of proliferative diabetic retinopathy. Here, we report on the novel diabetic pdx1(-/-) zebrafish mutant as a model for diabetic retinopathy that lacks the transcription factor pdx1 through CRISPR-Cas9-mediated gene knockout leading to disturbed pancreatic development and hyperglycemia. Larval pdx1(-/-) mutants prominently show vasodilation of blood vessels through increased vascular thickness in the hyaloid network as direct developmental precursor of the adult retinal vasculature in zebrafish. In adult pdx1(-/-) mutants, impaired glucose homeostasis induces increased hyperbranching and hypersprouting with new vessel formation in the retina and aggravation of the vascular alterations from the larval to the adult stage. Both vascular aspects respond to antiangiogenic and antihyperglycemic pharmacological interventions in the larval stage and are accompanied by alterations in the nitric oxide metabolism. Thus, the pdx1(-/-) mutant represents a novel model to study mechanisms of hyperglycemia-induced retinopathy wherein extensive proangiogenic alterations in blood vessel morphology and metabolic alterations underlie the vascular phenotype.
Die Zeichen "-/-" sind im Titel hochgestellt
Gesehen am 28.05.2020